Manajemen Kinerja Guru-Guru PJOK dalam Pembelajaran Pada SMP Negeri Di Kabupaten Takalar - Syahruddin Syahruddin; abdul rauf (Jurnal Penelitian Pendidikan, 2016)
Management is the key to lead a success in teaching and learning. This study aimed atdetermining how the management performance of PJOK (Sports and health Education)teachers in learning was. This was kind of descriptive research. The population of thisresearch were all teachers at SMP Negeri PJOK in Takalar within 38 teachers as thesample. Based on the available indicators that the lesson plan, teaching and learningprocess, and learning evaluation of PJOK teachers were relatively good. Briefly speaking,it can be concluded that the performance management of PJOK teachers in learning inSMP Takalar is quite good,